Managing mealybugs in cassava - International Center for Tropical Agriculture (2014)
Farmers in Thailand share practical tips to reduce the chance of mealybugs arriving in your cassava field. Special attention is paid to planting time; using healthy planting materials; disinfecting cassava stakes; protecting beneficial insects; and regularly observing the crop. This video is 16 minutes long and can be watched in Burmese, English, French, Indonesian, Khmer, Lao, Thai, and Vietnamese.